2014
DOI: 10.15171/ijhpm.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting family physicians’ drug prescribing: a cross-sectional study in Khuzestan, Iran

Abstract: In Khuzestan, the mean of medication per patient was fewer than national average. Approximately, pattern of prescribed drug by family physicians (including dosage form and type of drugs) was similar to other provinces of Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…We were still unable to fully explain the reasons for this prescriber variability even though we accounted for more higher levels characteristics compared to the other two studies [ 25 , 26 ]. Past studies had shown medical training and prescribers’ experience were associated with prescribing practices [ 39 , 40 ]. However, this does not appear to be so in our study, aside from the family medicine specialist which we postulate is due to the characteristics of the patients they see.…”
Section: Discussionmentioning
confidence: 99%
“…We were still unable to fully explain the reasons for this prescriber variability even though we accounted for more higher levels characteristics compared to the other two studies [ 25 , 26 ]. Past studies had shown medical training and prescribers’ experience were associated with prescribing practices [ 39 , 40 ]. However, this does not appear to be so in our study, aside from the family medicine specialist which we postulate is due to the characteristics of the patients they see.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the average number of drugs prescribed per prescription was 3.14, which is higher than the recommended optimum level (≤ 3). Studies in Iran have reported this index to be 2.6 to 4.11 [ 10 , 15 – 17 , 22 , 23 ]. In a national study, the average number of drugs per prescription was reported to be 3.07 (for all specialties) and 3.3 for general practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the payment may decrease if the physicians cannot preserve and maintain the assigned population, which may result in physicians' dissatisfaction (30). Delayed payments and low levels of bonuses are also regarded as reasons for physicians' dissatisfaction (31). One of the strengths of targeted payments is to encourage physicians to meet the desired standards of care and population health.…”
Section: Discussionmentioning
confidence: 99%